Organotins in Neuronal Damage, Brain Function, and Behavior: A Short Review - Ferraz da Silva, Igor; Freitas-Lima, Leandro Ceotto; Graceli, Jones Bernardes; Rodrigues, Lívia Carla de Melo (Frontiers in Endocrinology, 2018)
The consequences of exposure to environmental contaminants have shown significant effects on brain function and behavior in different experimental models. The endocrine-disrupting chemicals (EDC) present various classes of pollutants with potential neurotoxic actions, such as organotins (OTs). OTs have received special attention due to their toxic effects on the central nervous system, leading to abnormal mammalian neuroendocrine axis function. OTs are organometallic pollutants with a tin atom bound to one or more carbon atoms. OT exposure may occur through the food chain and/or contaminated water, since they have multiple applications in industry and agriculture. In addition, OTs have been used with few legal restrictions in the last decades, despite being highly toxic. In addition to their action as EDC, OTs can also cross the blood–brain barrier and show relevant neurotoxic effects, as observed in several animal model studies specifically involving the development of neurodegenerative processes, neuroinflammation, and oxidative stress. Thus, the aim of this short review is to summarize the toxic effects of the most common OT compounds, such as trimethyltin, tributyltin, triethyltin, and triphenyltin, on the brain with a focus on neuronal damage as a result of oxidative stress and neuroinflammation. We also aim to present evidence for the disruption of behavioral functions, neurotransmitters, and neuroendocrine pathways caused by OTs.